Thermodynamic regularities of deoxidation processes and technology of cord steel production - I. V. Ivanov; D. S. Jakshuk; V. V. Filippov; E. I. Leinveber; A. N. Parshikov (Литьë и металлургия)
Technology of differentiated deoxidation of cord types of steel is worked out, allowing to reduce non-metallic steel pollution and, as a result, to reduce end breakage at metal cord laying.